Association between nutritional risk, hospital stay and medical diagnosis among patients from a Peruvian social security hospital - Jauregui Romero, Erika (2023)
Objective: To determine the association between nutritional risk, hospital stay and medical diagnosis among patients admitted at Centro Especializado de Rehabilitación Profesional (CERP) of Hospital Nacional Guillermo Almenara Irigoyen. Materials and methods: An observational retrospective longitudinal cohort study was conducted with inpatients between July 1, 2021 and February 27, 2022. The patients were followed up until they left the hospital (discharge). Individualsunder 18 years of age, pregnant or puerperal women, and those whose stay was less than 24 hours were excluded. The data of interest was collected from the patients’ medical records and diet cards. The main variable was the nutritional risk, which was detected using the Nutritional Risk Screening (NRS) 2002. The secondary variables were age group, sex, hospitalstay, main medical diagnosis, discharge condition and nutritional status. Data analysis was performed using the chi-square test to compare the qualitative or categorical variables, and the Student’s t-test and ANOVA for the quantitative variables. A value of p < 0.05 was considered as statistically significant. Results: A total of 1,929 patients were included in the study. Nutritional risk prevalence accounted for 33.13 %. Patients with this condition showed the highest mortality rates (57.51 %). It was found that nutritional risk prevalence was related to a longer hospital stay (4.6 more days) (p < 0.001), a diagnosis of constitutional thinness (48.67 %) (p < 0.001) and themedical diagnosis, being oncology disorders the most associated ones (50.93 %). Conclusions: Nutritional risk is associated with disease progression, resulting in an increased hospital stay, mortality rate and therefore hospital costs. Early detection is important to provide adequate dietary interventions.